2014
DOI: 10.2147/imcrj.s62100
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin-induced deep vein thrombosis

Abstract: We are presenting a 72-year-old female who was admitted to hospital with deep vein thrombosis (DVT). She was known to have atrial fibrillation and was initiated on warfarin for stroke prophylaxis 3 days earlier. She was given warfarin therapy without low molecular weight heparin cover as per “slow-start regimen” protocol. The warfarin dose was increased after 3 days to achieve rapid anticoagulation, resulting in DVT in the left leg. We propose that the higher unopposed warfarin dose utilized in this case resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Time spent in the therapeutic range of warfarin is highly variable in clinical practice and was not frequently reported in the clinical trials except in one study that showed higher incidence of TE in patients with lower INR 5. The highly variable pharmacokinetics of warfarin and the fact that it also significantly diminishes levels of key vitamin K-dependent anticoagulants (ie, proteins C and S) prompt the need to study alternative agents that overcome these barriers 27. Whether the newer oral anticoagulants with superior pharmacokinetics and very high specificity that have been shown to be excellent alternatives to warfarin in other contexts would be used in preventing Fontan-associated TE remains to be determined 28 29.…”
Section: Discussionmentioning
confidence: 99%
“…Time spent in the therapeutic range of warfarin is highly variable in clinical practice and was not frequently reported in the clinical trials except in one study that showed higher incidence of TE in patients with lower INR 5. The highly variable pharmacokinetics of warfarin and the fact that it also significantly diminishes levels of key vitamin K-dependent anticoagulants (ie, proteins C and S) prompt the need to study alternative agents that overcome these barriers 27. Whether the newer oral anticoagulants with superior pharmacokinetics and very high specificity that have been shown to be excellent alternatives to warfarin in other contexts would be used in preventing Fontan-associated TE remains to be determined 28 29.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our sensitivity analysis identified a bidirectional causal effect between warfarin treatment and DVT. This would make sense, as individuals who are prescribed warfarin are more likely to already suffer from a form of VTE (2,33).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that, compared with other vitamin K-dependent proteins, the blood concentration of PS in this patient was relatively decreased. Although PS is a vitamin K-dependent coagulation factor, the antigen and activity of which are significantly reduced upon the initiation of warfarin therapy [ 69 – 71 ], its concentration is also decreased during long-term anticoagulation with warfarin [ 72 75 ]. Consequently, an accurate diagnosis of PS deficiency based on its blood concentrations may be challenging.…”
Section: Discussionmentioning
confidence: 99%